Rohime is new CEO of Proton Edar: EXPERIENCED LEADER: Tasked with reviving company's sales, market share. - News Straits, Times (News Straits Times, 2016)
PROTON Holdings Bhd has appointed Rohime Shafie as chief executive officer (CEO) of Proton Edar Sdn Bhd, replacing Norzahid Mohd Zahudi, who resigned with immediate effect.